Polymorphism of Calpastatin gene and its effect on body weight of local sheeps - C Sumantri; R Diyono; A Farajallah; I Inounu (Jurnal Ilmu Ternak dan Veteriner, 2008)
The objectives of this research were to identify polymorphism of calpastatin gene and to investigate any association of calpastatin genotype on body weight of local sheeps. A total number of DNA samples were collected from 288 heads of local sheeps from 8 populations. Two local sheep samples were medium tail sheeps (MTSs) of a Garut fighting type from Ciomas/Bogor (29) and a Garut meat type from Margawati (29). The remaining six local sheep population were one thin tail sheep (TTS) from Jonggol (36); and five fat tail (FTSs) from Indramayu (43), Madura (43), Sumbawa (26), Rote (36) and Donggala (46) respectively. Genomic DNAs of those blood of local sheeps were extracted by a standard phenol-chloroform protocol and amplified using a polymerase chain reaction (PCR) technique. PCR reaction was carried out in a thermocycler (Takara PCR of Thermal Cycler MP4) and PCR products were digested with Msp 1 enzyme restriction using a Restriction Fragment Length Polymorphism (RFLP) technique. The PCR-RFLP products were separated at 8% polyacrylamide gel electrophoresis (PAGE).  A silver-staining method then was applied to detect fragments. Genetic variations between local sheep populations were calculated based on frequencies of genotypes and alelles. The association between genotype of calpastatin gene and body weight of local sheeps were calculated by General Linear Model method by SAS version 6.12. A length of 622 base pairs (bp) of the calpastatin gene of the Indonesian local sheeps was successfully amplified by the PCR technique. An MspI restriction enzyme cut the PCR product into two different length fragments, those were 336 bp and 286 bp designated as M allele of the CAST-Msp1; whilst that unsuccessfully cut PCR product resulted one fragment 622 bp designated as N allele of the CAST-Msp1. Locus of the CAST-Msp1 gene in most local sheeps studied was polymorphic, the exception was in the FTS from Rote of which monomorphic. The highest frequency of the M allele was in the fighting Garut sheep from Ciomas (0.29), whilst the lowest was in the FTS from Rote (0.00). However, frequencies of the M allele of FTSs from Sumbawa and Madura were similar (0.04). Further, frequencies of the M allele of local sheeps from Margawati, Jonggol, Indramayu, and Donggala were 0.24, 0.16, 0.13 and 0.12 respectively. The highest frequency of MN genotype was observed in the Garut fighting sheep from Ciomas (0.58), but the lowest was in the FTS from Rote (0.00). The heterosigosity was observed differently  among populations. The highest heterosigosity was also identified in the Garut fighting sheep in Ciomas (0.43), whilst FTSs both in Sumbawa and Madura were for the lowest (0.08). Results of this study showed that there was a definit association betwen calpastatin genotype and body weight of male sheeps from which the MN genotype significantly related to a higher body weight compared to that of the NN genotype. Key Words : Local Sheeps, Calpastatin Gene, Polymorphism, Live Weight